HUMAN RIGHTS VIOLATIONS PERPETRATED BY STATE AGENTS IN MILITARY OCCUPATIONS: ANALYSIS OF THE INCURSION OF INTERNATIONAL HUMAN RIGHTS LAW TO THE NORMATIVE TERRITORY OF THE ARMED CONFLICTS - Sidney Cesar Silva Guerra; Luz E. Nagle; Ádria Saviano Fabricio da Silva (Revista Opinião Jurídica, 2021)
Objectives: This article aims to revisit the interrelationship between International Humanitarian Law (IHL) and International Human Rights Law (IHRL), in honour of their respective normative scopes and in order to carry out an analysis of their complementary or supplementary application, towards the construction of a more appropriate tool for the protection of human beings in extreme situations, as it occurs during armed conflicts. This is because, amid the multifaceted vulnerabilities that accumulate in today's conflicts, it is essential to provide the most effective source of protection - proportional to the demands for protection that are manifested today, particularly in military occupations around the world, whose occurrence will be the focus of this research.